Experiences of Religious Pluralism in Thailand: Lessons for Southeast Asian Countries - Montri Kunphoommarl (UNHI PRESS, 2019)
This paper used the historical approach to overview the patterns and practices of religious pluralism in Thai context. The past research work on religious pluralism will be examined in order to find out what concepts and approaches have been used and how they could implement in reality. Most Thai people practice in Buddhism, and they do not have any conflicts with other Thai Muslims or Christian. They live peacefully and harmoniously in co-existence among different religious adherents. The case of Thai Buddhist and Thai Muslim live together happily in the Southern communities will be employed and discussed using social and cultural capital analytical approach. The factors and conditions concerning with religious pluralism are analyzed more in details. The applications of religious pluralism in the study to other Southeast Asian countries will also recommend.